Multiple aspects of energy poverty are associated with lower mental health-related quality of life: A modelling study in three peri-urban African communities - Shupler, Matthew; Baame, Miranda; Nix, Emily; Tawiah, Theresa; Lorenzetti, Federico; Saah, Jason; Anderson de Cuevas, Rachel; Sang, Edna; Puzzolo, Elisa; Mangeni, Judith; Betang, Emmanuel; Twumasi, Mieks; et al. (SSM-Mental Health, 2022)
Over 900 million people in sub-Saharan Africa (SSA) live in energy poverty, relying on cooking polluting fuels (e.g. wood, charcoal). The association between energy poverty and mental/physical health-related quality of life (HRQoL) among women in SSA, who are primarily tasked with cooking, is unknown. Methods: Females (n ¼ 1,150) from peri-urban Cameroon, Kenya and Ghana were surveyed on their household energy use and mental/physical health status using the standardized Short-Form 36 (SF-36) questionnaire. Random effects linear regression linked household energy factors to SF-36 mental (MCS) and physical component summary (PCS) scores. A binary outcome of ‘likely depression’ was derived based on participants' MCS score. Random effects Poisson regression with robust error variance assessed the relationship between household energy factors and odds of likely depression. Results: The prevalence of likely depression varied by a factor of four among communities (36%-Mbalmayo, Cameroon; 20%-Eldoret, Kenya; 9%-Obuasi, Ghana). In the Poisson model (coefficient of determination (R2) ¼ 0.28), females sustaining 2 or more cooking-related burns during the previous year had 2.7 (95%CI:[1.8,4.1]) times the odds of likely depression as those not burned. Females cooking primarily with charcoal and wood had 1.6 times (95%CI:[0.9,2.7]) and 1.5 times (95%CI:[0.8,3.0]) the odds of likely depression, respectively, as those primarily using liquefied petroleum gas. Women without electricity access had 1.4 (95%CI:[1.1,1.9]) times the odds of likely depression as those with access. In the MCS model (R2 ¼ 0.23), longer time spent cooking was associated with a lower average MCS score in a monotonically increasing manner. In the PCS model (R2 ¼ 0.32), women injured during cooking fuel collection had significantly lower ( 4.8 95%CI:[-8.1,-1.4]) PCS scores. Conclusion: The burden of energy poverty in peri-urban communities in SSA extends beyond physical conditions. Experiencing cooking-related burns, using polluting fuels for cooking or lighting and spending more time cooking are potential risk factors for lower mental HRQoL among women.
Keywords: SF-36; Health-related quality of life; Energy poverty; Electricity; Clean cooking; LPG; Burns